“Fertilización con N-P-K aplicada en tres dosis en el cultivo de pijuayo para palmito Bactris gasipaes H.,en suelos Ácidos-Distrito de pongo de cainarachi provincia de Lamas” - Águila Castañeda, Enrique Ernesto Del (2014)
This research work entitled "Fertilization with NPK applied in three doses in growing peach palm to palm Bactris gasipaes h in acid soils - District Pongo de Cainarachi province of Lamas" had the specific objective to evaluate and study the effect three doses of NPK on the production and I or crop productivity of peach palm fer palm hearts, and establish the cost benefit of the treatments. Design Randomized Complete Block (RCBD) with four blocks and four treatments was used. The dese of each treatment were: T1: Control; T2: 100 N - 60 P20 5 - 220 K20; T3: 200 N - 60 P20 5 - 220 K20; T4: 400 N - 60 P20s - 220 K20. The results indicate a positive and proportional to the amount or dese of chemical fertilizer applied, and the inherence of mycorrhizal fungi, their adaptation to soil and climatic conditions in each of the treatments, increasing influence production was recorded. Fertilizer application at doses of T3 (N - P - K, 200 N - 60 P20s -220 K20, respectively), increases production and generate higher returns. Economically the T3 (200 N - 60 P205 - 220 K20) is the recommended treatment fer fertilizing palm plantations in the district Pongo Cainarachi generate 100% more profitable investment. Keywords: Fertilization, dese, production, productivity, effect, inherence, fungi, mycorrhizal, adaptation, soil and climate.